Inhibitory control deficits in patients with mesial temporal lobe epilepsy: an event-related potential analysis based on Go/NoGo task - Shao, Chenjing; Li, Desheng; Zhang, Xu; Xiang, Feng; Zhang, Xi; Wang, Xiangqing (Frontiers in Neurology, 2024)
Objective Neuropsychiatric comorbidities are common among patients with mesial temporal lobe epilepsy (MTLE). One of these comorbidities, impulsivity, can significantly impact the quality of life and prognosis. However, there have been few studies of impulsivity in these patients, and the existing findings are inconsistent. The present study investigates impulsivity in MTLE patients from the perspective of inhibitory control and its underlying processes using event-related potentials (ERPs) initiated using a Go/NoGo task. Methods A total of 25 MTLE patients and 25 age-, gender-, and education-matched healthy controls (HCs) completed an unequal visual Go/NoGo task. Different waveforms as well as behavioral measures were analyzed between Go and NoGo conditions (N2d and P3d). Impulsivity was also assessed using self -rating scales, and clinical variables that may be related to ERPs were explored. Results Compared with HCs, MTLE patients exhibited significantly longer reaction time (RT) (p = 0.002) and lower P3d especially at the frontal electrode sites (p = 0.001). In the MTLE group, the seizure frequency (p = 0.045) and seizure types (p < 0.001) were correlated with the P3d amplitude. A self-rated impulsivity assessment revealed that MTLE patients had higher non-planning (p = 0.017) and total scores (p = 0.019) on the BIS-11 as well as higher DI (p = 0.010) and lower FI (p = 0.007) on the DII. Conclusion The findings demonstrate that the presence of inhibitory control deficits in patients with MTLE are characterized by deficits in the late stage of inhibition control, namely the motor inhibition stage. This study improves our understanding of impulsivity in MTLE patients and suggests that ERPs may constitute a sensitive means of detecting this trait.